The market as institutionalization of irresponsibility: An ethical reflection on free market capitalism - Urbina Padilla, Dante Abelardo (2020)
This article is an ethical reflection on free market capitalism. It is maintained that the buyer-seller dynamics is based on and also generates selfish individuals who tend to forget the moral dimension of their actions in the market. The price system plays an important role in this respect since it eliminates qualitative differences among goods. The alleged moral justification of capitalism by appealing to liberty is also called into question.